Ablation resistance of ZrC-MoSi2/ZrC-SiC double-layered coating in a plasma flame. (December 2018) - Liu, Tao; Niu, Yaran; Li, Chong; Pan, Xiaohui; Shi, Minhao; Zheng, Xuebin; Ding, Chuanxian
Graphical abstract: Highlights: ZrC-MoSi2 /ZrC-SiC double-layered coating with excellent ablation resistance is firstly reported. SiC-depleted zone and bubble burst of MoO3 were found to be the fatal defects for ZrC-SiC and ZrC-MoSi2 coatings, respectively. Diffusion phenomenon of Si from ZM layer into ZS layer was observed and active oxidation of SiC was limited. Introduction of Si from decomposition of MoSi2 into ZrC-SiC layer is a promising way to solve the problem of SiC-depleted zone. Abstract: A double-layered composite coating was designed for optimizing the ablation resistance of ZrC coating, which contained external ZrC-SiC and inner ZrC-MoSi2 layers. The ablation resistance of the coating was evaluated and compared with the single-layered ZrC-SiC and ZrC-MoSi2 coatings. SiC-depleted zone and bubble burst of MoO3 were found to be the fatal defects for the ZrC-SiC and ZrC-MoSi2 coatings, respectively. For the double-layered coating, the external layer acted as oxygen diffusion barrier and the inner layer offered extra Si source for the external one. The double-layered design effectively reduced the destructive effect of SiC-depleted zone and bubble burst.